The structural nature of underdevelopment in Peru - Lust, Jan (2024)
Peru remains an underdeveloped country, although in recent decadesthe real Gross Domestic Product has increased substantially. The countrycannot develop if the structural conditions of underdevelopment have notbeen eliminated. One of the main reasons for Peru’s underdevelopment isthe country’s role in the globalized capitalist world as a provider of natural resources for economic development in the global north. This role is not theconsequence of their possession of abundant raw materials necessary forcapitalist development in this area, but rather the historical result of havingtheir own (capitalist) development disrupted by colonial exploitation andoppression. The current economic development model is closely relatedto Peru’s role in the international division of labor. The country’s economicand business structures are, in part, internal expressions of the country’sfunction in the globalized capitalist world. These economic and businessstructures do not allow economic progress and make current economicdevelopment unsustainable. The Peruvian State is a dependent capitaliststate, which has the general characteristics of the capitalist state and thecharacteristics that are a product of the country’s role in the capitalist worldsystem and the dependent nature of its economy. The main function ofthe dependent capitalist state is to reproduce the basic conditions for thefunctioning of the dependent national capitalist system.